Implementation and public acceptability: lessons from food irradiation and how they might apply to pathogen reduction in blood products. Issue 1 (12th February 2014) - Heddle, N. M.; Lane, S. J.; Sholapur, N.; Arnold, E.; Newbold, B.; Eyles, J.; Webert, K. E.
<x xml:space="preserve">Abstract</x> Background and Objectives The issues around food irradiation (FI) have both similarities and differences to pathogen reduction (PR) in blood products. We performed a systematic search of the FI literature to identify lessons that could help to inform the implementation of pathogen reduction technology for blood products. Methods A comprehensive literature search was performed in EMBASE. MEDLINE, PSYCHINFO, CINAL and Physiological Abstracts for articles related to FI that met predefined eligibility criteria. A coding scheme was developed by the investigators, and relevant information from the articles was coded using NVivo 9. Reports for each code were generated and summarized. Results One thousand two hundred and sixty‐six articles were identified by the broad search, and 50 met the study eligibility criteria for inclusion. The implementation of FI was slow and has been met by significant controversy, sparked by concerns from the public and social groups about the acceptability of irradiated food. Numerous factors influenced public acceptability including: demographic factors; perceptions of safety and risk; endorsement of and trust in the FI industry and social institutions that serve as opinion leaders; knowledge and the provision of scientific information including benefits and cost; and the availability of choice. Conclusion There are a number of lessons from the FI literature that may be generalizable to the implementation of PR of blood products. Based on findings from this study, six recommendations are made to facilitate public implementation of this new technology.